2010
DOI: 10.1186/1471-2296-11-96
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and hypertension guidelines and the primary health care practitioner in Barbados: knowledge, attitudes, practices and barriers-a focus group study

Abstract: BackgroundAudits have shown numerous deficiencies in the quality of hypertension and diabetes primary care in Barbados, despite distribution of regional guidelines. This study aimed to evaluate the knowledge, attitudes and practices, and the barriers faced by primary care practitioners in Barbados concerning the recommendations of available diabetes and hypertension guidelines.MethodsFocus groups using a moderator's manual were conducted at all 8 public sector polyclinics, and 5 sessions were held for private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…Externalities associated with plant pest management may be positive or negative and can be divided into short-and long-term ecological, social and economic components [1]. The economic theory suggests that rational economists would not only weigh the costs and short-term economic gains, but also the risks and benefits [25]. Hence, rational tea farmers as implementers of TEPM should weigh its benefits against its costs.…”
Section: Discussionmentioning
confidence: 99%
“…Externalities associated with plant pest management may be positive or negative and can be divided into short-and long-term ecological, social and economic components [1]. The economic theory suggests that rational economists would not only weigh the costs and short-term economic gains, but also the risks and benefits [25]. Hence, rational tea farmers as implementers of TEPM should weigh its benefits against its costs.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we provide similar evidence for a low resource setting. Conversely, there is research evidence that many service providers still do not follow the key recommendations in guidelines [ 25 , 35 37 ]. In these research studies, a lack of knowledge, inaccessibility and unavailability of the guidelines and a lack of support and enthusiasm for them were reported as the main obstacles to their implementation, and there was also a lack of follow up monitoring by the Government (or governing body) of specific implementation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Health care professionals who routinely see patients with diabetes offer a valuable perspective on reasons for ongoing gaps in diabetes care. To date, there have been no studies reporting health care professionals’ (HCP) perspectives on the barriers to achieving optimal care of persons with diabetes in the Caribbean, with the exception of Barbados where a previous qualitative study identified barriers at the level of the patient, healthcare professional, and health care system [ 10 ]. The perspectives of health care professionals in T&T may uniquely inform the design of future prevention strategies and are imperative to reduce the rising burden of diabetes in this country.…”
Section: Introductionmentioning
confidence: 99%